Heterothermy in a Small Passerine: Eastern Yellow Robins Use Nocturnal Torpor in Winter - Aharon-Rotman, Yaara; McEvoy, John F.; Beckmann, Christa; Geiser, Fritz (Frontiers in Ecology and Evolution, 2021)
Torpor is a controlled reduction of metabolism and body temperature, and its appropriate use allows small birds to adapt to and survive challenging conditions. However, despite its great energy conservation potential, torpor use by passerine birds is understudied although they are small and comprise over half of extant bird species. Here, we first determined whether a free-living, small 20 g Australian passerine, the eastern yellow robin (Eopsaltria australis), expresses torpor by measuring skin temperature (Ts) as a proxy for body temperature. Second, we tested if skin temperature fluctuated in relation to ambient temperature (Ta). We found that the Ts of eastern yellow robins fluctuated during winter by 9.1±3.9°C on average (average minimum Ts 30.1±2.3°C), providing the first evidence of torpor expression in this species. Daily minimum Ts decreased with Ta, reducing the estimated metabolic rate by as much as 32%. We hope that our results will encourage further studies to expand our knowledge on the use of torpor in wild passerines. The implications of such studies are important because species with highly flexible energy requirements may have an advantage over strict homeotherms during the current increasing frequency of extreme and unpredictable weather events, driven by changing climate.